Morphometric assessment of the hip joint in the Estrela Mountain Dog breed - Martins, J.; Ferreira, A. J.; Ginja, M. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objectives: To study the radiographic projected hip parameters of the proximal femur and acetabulum in young and adult Estrela Mountain Dogs with normal and abnormal hip joints. The parameters evaluated were: femoral angles of inclination and anteversion (FAI and FAA), femoral neck length and width (FNL and FNW), acetabular depth (AD) and acetabular angle of retrotorsion (AAR).Methods: Five hundred and twenty-five standard hip-extended ventrodorsal radiographic views and 622 mediolateral views of the right and left femur were used to measure the FAI, FAA, FNL, FNW, AD, AAR and modified AAR (mAAR).Results: The FAI decreased in adult dysplastic dogs, in females and in right femora; FAA decreased with age; FNL was characterized by a greater relative size in normal adult animals; FNW was greater in abnormal hips in young and adult animals; AD was less in adult dysplastic dogs and in right hips; AAR was similar in the studied groups; mAAR was greater in abnormal hips and in left hips.Clinical significance: The data may be used in future studies, which compare this breed to others. Morphological variations in femoral neck and acetabular morphometric parameters were present, and these variables in dogs with different ages and with hips in varying states of health should not be compared.
Keywords: Femoral angle of inclination; femoral angle of anteversion; femoral neck length; femoral neck width; acetabular depth; acetabular angle of retrotorsion